JENIS-JENIS MAKNA PADA LIRIK LAGU DALAM ALBUM COLOURS OLEH MICHAEL LEARNS TO ROCK - Ticoalu, Alvionita; Kodong, Fentje; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACT      This research aims at identify, classify, and analyze the kinds of meaning based on their forms and meanings. All of the data have been taken from song lyrics of the album Colours by Michael Learns to Rock and analyzed based on Leech’s theory (1981). The descriptive method is used in this research. The result of this research shows that kinds of meaning can be found in song lyrics. It is proved by the number of kinds of meaning which were identified in the lyrics: there are conceptual meaning, connotative meaning, social meaning, affective meaning, reflected meaning, collocative meaning and thematic meaning. Conceptual meaning shows the real meaning of the words, connotative meanings shows the meaning of the word is over and above its purely conceptual meaning, social meaning shows the meaning of the words that shows the social environment, affective meaning is how words reflect the personal feelings of the speaker, reflected meaning shows the meaning which arises in cases of multiple conceptual meaning, collocative meaning shows the meaning that consist of the associations a word requires of the meaning of words which tend to occur in its environment and thematic meaning shows how the speaker emphasizes the meaning of the words. This research can provide knowledge about the types of meaning in semantic studies, especially for another researcher. This research can be used as a reference for further research.Keywords: Kinds of Meaning, Song Lyrics, Album Colours by Michael Learns to Rock